2021
DOI: 10.4269/ajtmh.20-1378
|View full text |Cite
|
Sign up to set email alerts
|

House Structure Is Associated with Malaria among Febrile Patients in a High-Transmission Region of Zambia

Abstract: Since the late nineteenth century, the importance of house structure as a determinant of malaria risk has been recognized. Few studies to date have examined the association of housing and malaria in clinical populations. We conducted a cross-sectional study of febrile patients (n = 282) at two rural health clinics in a high malaria-transmission area of northern Zambia. Participants underwent testing for Plasmodium falciparum infection by PCR. Demographic and other risk factors including house structure, indoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 64 publications
(84 reference statements)
2
9
0
Order By: Relevance
“…However, adopting this strategy to reduce and control malaria mainly depends on the government’s and global partners’ strategies to enhance economic growth and ultimately improve the SES of the families. Previous studies showed that apart from their inability to afford better or improved houses, poor families also fail to adopt and effectively use other malaria interventions (such as access to better health care services, and ownership and use of bed nets) leaving them at increased risk of the disease as well as perpetuating the transmission in the community [7375]. Therefore, specific interventions are urgently needed to target poor families in the fight against malaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, adopting this strategy to reduce and control malaria mainly depends on the government’s and global partners’ strategies to enhance economic growth and ultimately improve the SES of the families. Previous studies showed that apart from their inability to afford better or improved houses, poor families also fail to adopt and effectively use other malaria interventions (such as access to better health care services, and ownership and use of bed nets) leaving them at increased risk of the disease as well as perpetuating the transmission in the community [7375]. Therefore, specific interventions are urgently needed to target poor families in the fight against malaria.…”
Section: Discussionmentioning
confidence: 99%
“…However, adopting this strategy to reduce and control malaria mainly depends on the government's and global partners' strategies to enhance economic growth and ultimately improve the SES of the families. Previous studies showed that apart from their inability to afford better or improved houses, poor families also fail to adopt and effectively use other malaria interventions (such as access to better health care services, and ownership and use of bed nets) leaving them at increased risk of the disease as well as perpetuating the transmission in the community [73][74][75] In the study areas, most of the participants (over 96%) reported owning and using bed nets and the prevalence and risk of malaria infections were similar in those with as well as without/not using bed nets. Studies have shown that with high bed net coverage, even non-users and the entire community may be protected against malaria because high coverage of ITN/LLINs in the community and their use lead to a reduction of the number of mosquitoes, their length of survival and eventually their ability to transmit malaria [76,77].…”
Section: Discussionmentioning
confidence: 99%
“… 54 Other risk factors were less context-specific: younger age, male sex, low-quality housing, living at lower elevation, higher rainfall, warmer weather, and lower educational attainment of the head of household were associated with higher malaria risk. 53 55 Using a mosquito net and living in a household with more nets per occupant were protective against malaria. 53 55 In hospitalized children with malaria, blood stockouts and referral from a village or health center further from the hospital were associated with higher inpatient mortality.…”
Section: Refractory High-level Malaria Transmission In Northern Zambiamentioning
confidence: 99%
“… 53 55 Using a mosquito net and living in a household with more nets per occupant were protective against malaria. 53 55 In hospitalized children with malaria, blood stockouts and referral from a village or health center further from the hospital were associated with higher inpatient mortality. 56 Whole blood transfusion was associated with improved survival in children with severe malarial anemia, and transfusion using whole blood stored > 28 days was no better than no transfusion.…”
Section: Refractory High-level Malaria Transmission In Northern Zambiamentioning
confidence: 99%
“…There has been indication that the relationship between household structure and malaria risk is actually a mediating one between the true relationship between household income and education and P. falciparum infection ( 20 ). The underlying hypothesis in this relationship is that the head of household education level and income level are associated with household structure, which is then associated with P. falciparum infection.…”
Section: Introductionmentioning
confidence: 99%